Two new species of Atopophlebia Flowers, 1980 (Ephemeroptera, Leptophlebiidae) from Colombia - Salles, F.f.; Marulanda, J.f.; Dias, L.g. (Zootaxa, 2018)
Atopophlebia pacis sp. nov. and Atopophlebia caldasi sp. nov. are newly described based on material from Colombia, Putumayo and Caldas, respectively. Both species are known from nymphs and alate stages, male imago for A. pacis, male subimago, female imago and eggs for A. caldasi. This is the first description of eggs of the genus. The following characteristics are useful for distinguishing the males of the new species: A. pacis sp. nov., 1) eyes meeting on meson of head; 2) fore wings hyaline, veins yellow (Fig. 2); 3) fore tibia completely tinged with black; 4) abdominal segments yellowish, terga VIII with conspicuous triangular anterolateral black mark (Fig. 1); 5) apical projection of penis lobe short; A. caldasi sp. nov., 1) eyes meeting on meson of head; 2) fore tibia completely tinged with black; 3) abdominal segments orange, posterior margin of all terga tinged with black, black bands broader on terga V to VIII. Egg of A. caldasi is characterized by presenting a prismatic shape with longitudinal chorionic depressions at the sides and concave polar regions. An updated key for male adults of Atopophlebia is presented.